Performance Evaluation of the Thai Agricultural Cooperatives - Suebpongsakorn, Auttapol (Journal of Applied Economics and Management Strategy, 2021)
The aims of this research are to measure the efficiency of the Thai agricultural cooperatives and provide the policy recommendation for these firms. Due to the multiple business functions of agricultural cooperatives, DEA technique called Super SBM–O–V is employed to handle this problem. Data for all inputs and outputs from Cooperative Auditing Department (CAD) are collected for 77 DMUs, which are the representatives of 77 provinces in Thailand. In this case, Operating capital per member and total expenses per member were treated as input variables, since they represented amount of resources used for running the daily operations, while value of the main 5 businesses per member of agricultural cooperatives including (deposit, credit, trading, compilation of products and service and agricultural support) are used as the output variables, since all of these variables represented the value generated by cooperatives. The results showed that only 23 DMUs are operated on the efficiency frontier, while the rest of 54 DMUs are inefficient. The top 5 provinces that have the largest TE score consist of Chon Buri, Chanthaburi, Krabi, Amnat Charoen, and Phetchaburi, while the bottom 5 provinces with the lowest TE score include Trat, Nonthaburi, Loei, Nakhon Nayok, and Ang Thong. The average TE score of overall 77 provinces in Thailand is 0.6120. The computed slacks of inefficient DMUs provides useful information of how to improve the efficiency score of each DMU.